2002
DOI: 10.1590/s0041-87812002000600007
|View full text |Cite
|
Sign up to set email alerts
|

Thumb metastasis from small cell lung cancer treated with radiation

Abstract: A rare case of thumb metastasis from small cell lung cancer is presented. The patient underwent local radiotherapy with complete palliation of symptoms. She died 4 months later with disseminated disease. Considerations about incidence, treatment, and physiopathology of this kind of dissemination are made. Conservative treatment of finger metastasis with radiation may be considered due to the poor outcome of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…8 Other possible differential diagnoses can be evoked: cartilaginous matrix tumors, rheumatoid arthritis and gout. 9,14,17 The absence of a known primary neoplasia, should lead to perform a systematic chest x-ray or even a chest CT scan to look for bronchopulmonary neoplasia even if the patient is asymptomatic. 8 The management of these patients depends on the extent of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other possible differential diagnoses can be evoked: cartilaginous matrix tumors, rheumatoid arthritis and gout. 9,14,17 The absence of a known primary neoplasia, should lead to perform a systematic chest x-ray or even a chest CT scan to look for bronchopulmonary neoplasia even if the patient is asymptomatic. 8 The management of these patients depends on the extent of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…First, this diagnosis is rare. [5][6][7][8][9] Second, these patients typically present with swelling, erythema, tenderness or loss of function, suggesting a long list of possible diagnoses. Most commonly this presentation suggests an infectious process.…”
Section: Discussionmentioning
confidence: 99%
“…2 Systemic chemotherapy or radiation can be used in cases in which amputation causes the patient to lose hand function and in cases with proximal lesions or multiple lesions. 2,4,7,8 Palliative short course radiation can provide pain relief and help maintain normal hand function. Unfortunately, regardless of the type of treatment, the prognosis of these patients is very poor because acrometastasis generally accompanies widespread disease.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,20 Metastatic malignancies of the hand are rare and they usually develop from the lung. 21,22 Bone metastasis of hepatocellular carcinoma to the hand is very rare and there are only four cases in the literature. Reichbach et al 1 reported the fi rst case of metastatic lesion of the distal phalanx of the thumb from primary hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%